Exterior rotor permanent magnet generator in variable speed applications - Sattar, Rauf (2016)
This thesis explores approaches for converting rotational mechanical power from diesel engines into electrical power of fixed frequency and voltage. Advances in high energy permanent magnets and power electronics are enabling technologies that provide opportunities for electrical machines with increased efficiency and compact size for variable speed power generation.